Effects of Cereal Bran Addition on Chemical Composition, Cooking Characteristics and Sensory Properties of Turkish Meatballs¶ - EBRU YASARLAR, ELIF; DAGLIOGLU, ORHAN; YILMAZ, ISMAIL (Asian Journal of Chemistry, 2010)
In this study, cereal brans (oat, maize, rye and wheat) were used as dietary fibre source in the production of meatballs. The effects of bran addition on chemical composition, weight losses, dietary fibre content, colour (L, a and b values) and sensory properties of Turkish type meatballs were studied. Meatball samples were produced with four different formulations including of 5, 10, 15 and 20 % bran addition and bran added samples were compared with the control meatballs. The control meatballs had the highest weight losses. Meatballs with added bran had lower L, a and b values than control samples. There was significant decrease (p < 0.05) among sensory properties of meatballs in respect to bran addition. Control samples and 10 % corn bran added samples had the highest overall acceptability scores and 15 % of corn bran addition also led to acceptable products.